ICCREM 2017. proceedings of the International Conference on Construction and Real Estate Management 2017, November 10-12 2017, Guangzhou, China - Wang, Yaowu; Pang, Yongshi; Shen, Qiping; Zhu, Yimin (College teacher) (American Society of Civil Engineers, 2017)
This collection contains 42 peer-reviewed papers on project management and construction technology. Topics include: risk assessment in construction projects; BIM-based analysis and the assessment of projects; and information management and project teams.
Keywords: Construction industry -- Management -- Congresses.; Construction industry -- Technological innovations -- Congresses.; Building information modeling -- Congresses.; elektronické knihy; electronic books